Metadynamics supports molecular dynamics simulation-based binding affinities of eucalyptol and beta-cyclodextrin inclusion complexes. Issue 80 (1st November 2017) - Nutho, Bodee; Nunthaboot, Nadtanet; Wolschann, Peter; Kungwan, Nawee; Rungrotmongkol, Thanyada
Abstract : The development of various molecular dynamics methods enables the detailed investigation of association processes, like host–guest complexes, including their dynamics and, additionally, the release of the guest compound. Abstract : The development of various molecular dynamics methods enables the detailed investigation of association processes, like host–guest complexes, including their dynamics and, additionally, the release of the guest compound. As an example of the application of such methods, the inclusion complexation of cyclodextrins with eucalyptol is described. Eucalyptol is the major constituent of eucalyptus oil, which exhibits anti-inflammatory properties. This compound has many applications including flavors, fragrances and medical therapies. However, its pharmaceutical applications are limited due to volatility and low water solubility. Cyclodextrins (CDs) are compounds that are capable of forming inclusion complexes with eucalyptol to enhance solubility and stability. In the present work, molecular dynamics (MD) simulations and free energy calculations were performed to determine the molecular structure, dynamical behaviour and binding affinities of the host–guest inclusion complexes of eucalyptol with native beta-cyclodextrin (βCD) and its derivatives, 2, 6-dimethyl-βCD (2, 6-DMβCD) and the three hydroxypropyl-βCDs (2-HPβCD, 6-HPβCD and 2, 6-DHPβCD). In the inclusion complex, eucalyptol preferentially locates within the hydrophobic cavity with all βCDs studied here. The binding affinities were calculated by MM/PBSA and QM/PBSA with the M06-2X/6-31G(d, p) level of theory and are in relatively good agreement with the experimental stability constants in the order of 2, 6-DMβCD > βCD > 2-HPβCD. In addition, recently developed metadynamics simulations were applied to investigate the eucalyptol's release pathways from the cavity of the CDs. The results from this study show that MD simulations, metadynamics and related free energy calculations provide an excellent support for experimental studies, and they give additional information about the structural and dynamical behaviour of inclusion complexes as well as the energetic details about host–guest interactions. Moreover, the releasing direction and possible dissociation rates of the inclusion complexes were also predicted.